Studies on the molecular phylogenies of some malaria - like parasites from non-human hosts in Malaysian Borneo - Yau, Monica Swee Eng. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
The aim of this study is to identify and characterize haemosporidian parasites (Phylum Apicomplexa, family Plasmodiidae) from non-human hosts in Borneo. The information generated will contribute to the expansion of the available sequences to build molecular phylogenies of malaria species. Total of 100 blood samples were collected from small mammals from nine locations in Malaysian Borneo.